In Vitro Comparison of 2 Clinically Applied Biomaterials for Autologous Chondrocyte Implantation: Injectable Hydrogel Versus Collagen Scaffold. (June 2023) - Weitkamp, Jan-Tobias; Benz, Karin; Rolauffs, Bernd; Bayer, Andreas; Weuster, Matthias; Lucius, Ralph; Gülses, Aydin; Naujokat, Hendrik; Wiltfang, Jörg; Lippross, Sebastian; Hoffmann, Michael; Kurz, Bodo; et al.
Objective: In autologous chondrocyte implantation (ACI), there is no consensus about used bioscaffolds. The aim of this study was to perform an in vitro comparative analysis of 2 clinically applied biomaterials for cartilage lesion treatment. Design: Monolayer expanded human chondrocytes ( n = 6) were embedded in a collagen scaffold (CS) and a hyaluronic acid–based hydrogel (HA). Cells were cultured in chondropermissive medium supplemented with and without interleukin-10 (IL-10) and bone morphogenetic protein–2 (BMP-2). Gene expression of chondrogenic markers (COL1A1, COL2A1, COL10A1, ACAN, SOX9) was detected via quantitative real-time–polymerase chain reaction (RT-qPCR). Biosynthesis of matrix compounds, cell viability, morphology as well as migration from surrounding native bovine cartilage into cell-free scaffolds were analyzed histologically. Adhesion of the material to adjacent cartilage was investigated by a custom-made push-out test. Results: The shift of COL1/2 ratio toward COL2A1 was more pronounced in HA, and cells displayed a more spherical morphology compared with CS. BMP-2 and IL-10 significantly increased COL2A1, SOX9, and ACAN expression, which was paralleled by enhanced staining of glycosaminoglycans (GAGs) and type 2 collagen in histological sections of CS and HA. COL10A1 was not significantly expressed in HA and CS. Better interfacial integration and enhanced cell invasion was observed in CS. Push-out tests using CS showed higher bonding strength to native cartilage. Conclusion: HA-based hydrogel revealed a more chondrocyte-like phenotype but only allowed limited cell invasion, whereas CS were advantageous in terms of cellular invasion and interfacial adhesion. These differences may be clinically relevant when treating cartilaginous or osteochondral defects.